A Computer Generated Induction System for Hospitalized Patients Starting on Oral Anticoagulant Therapy - Ageno, Walter; Johnson, Judith; Nowacki, Barbara; Turpie, Alexander G.G. (Thrombosis and Haemostasis, 2000)
There is an increasing use of computer-based dosage programs to monitor oral anticoagulant therapy in outpatients. DAWN AC INDUCTION by 4S, UK, is a computer generated system to initiate oral anticoagulant therapy providing fast access to the maintenance program. This method of initiation of anticoagulant therapy has not been validated. We therefore randomized 50 hospitalized patients starting oral anticoagulation to control by the computer and 51 by manual dosing using a dosing schedule based on a locally defined algorithm. After a 7 days follow up, the daily mean INR was 2.09 and 2.07 and the proportion of dose adjustments was 48% and 45% in the computer and manually controlled groups respectively. Twenty-eight % of the patients monitored by the computer system required at least one manual overriding. DAWN AC INDUCTION provided a simple and accurate organization of the data, with an overall quality comparable to that of the manual system. Furthermore, the induction programme provided simple access to the maintenance programme. Although it required careful monitoring, the programme resulted in a significant saving in personnel time.
Keywords: Warfarin; computer management